PENGARUH PEMBAYARAN GAJI DAN INSENTIF TERHADAP KINERJA GURU DI SMK WIYATA MANDIRI PAGERBARANG KABUPATEN TEGAL - Iskandar Iskandar (Jurnal Strategik, 2017)
ABSTRACT This research entitled "The Effect of Salary and Incentives for Teacher's performance at Wiyata Mandiri Vocational School in Tegal Regency Pagerbarang". This research aims to: 1. To find out how good it is to influence the level of study on the performance of teachers at the Wiyata Vocational School in Bandung, North Sumatra, Tegal. 2. To recognize the effect of giving Partial Incentives to teacher performance at Wiyata Vocational School in Bandung, North Sumatra District, Tegal. 3. To find out how the effect of giving Salary and Incentives Simultaneously to the performance of teachers at Wiyata Mandiri Vocational School Pagerbarang, Tegal Regency. 4. To find out the dominant influence on teacher performance at Wiyata Mandiri Vocational School in Tegal Regency Pagerbarang. From the results of the research that has been carried out at the Wiyata Mandiri Vocational School in Tegal regency, the following conclusions can be drawn: 1. Based on the results of the partial hypothesis test (t test), the results of t arithmetic for the Salary variable (X1) are 1,230 with a sig value of 0.092> 0.05, while for the incentive variable (X2) the value of t is 5.570 with a sig value of 0.072> 0.5 of these results, it can be concluded that for the hypothesis one only the Incentive variable (X2) has a significant effect on performance while the Salary variable (X1) does not have a dominant effect on the performance of SMK Teachers Wiyata Mandiri Pagerbarang, Tegal Regency 1. Based on the results of the simultaneous test (f test) obtained the results of F count of 869,721 with a sig value of 0,000 0.988), it can be concluded that salary has a dominant influence on teacher performance at the Wiyata Mandiri Vocational School in Tegal Regency Pagerbarang ..